2015
DOI: 10.1016/j.ccell.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Adult Lineage-Restricted CNS Progenitors Specify Distinct Glioblastoma Subtypes

Abstract: Summary A central question in glioblastoma multiforme (GBM) research is the identity of the tumor-initiating cell, and its contribution to the malignant phenotype and genomic state. We examine the potential of adult lineage restricted progenitors to induce fully penetrant GBM using central nervous system (CNS) progenitor-specific inducible Cre mice to mutate Nf1, Trp53 and Pten. We identify two phenotypically and molecularly distinct GBM subtypes governed by identical driver mutations. We demonstrate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 42 publications
4
111
0
1
Order By: Relevance
“…While these two molecular subtypes appear similar on a histopathological level, their expression profiles suggest that they might have disparate cellular origins. Recent elegant mouse modeling studies (Alcantara Llaguno et al, 2015) suggests that both multipotent neural stem cells (NSCs) and lineage-restricted oligodendrocyte precursor cells (OPCs) are capable of giving rise to anatomically and molecularly unique types of GBM when transformed with identical mutations (i.e., Tp53 , Pten , Nf1 deletion) using cell specific Cre-drivers ( Nestin creER for NSCs, Ascl1 creER for NSC/OPCs, Cspg4 creER for OPCs). These authors observed expression of Olig2 in both Type I (‘NSC’-like) and Type II (‘OPC-like’) tumors in their genetically engineered mouse models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these two molecular subtypes appear similar on a histopathological level, their expression profiles suggest that they might have disparate cellular origins. Recent elegant mouse modeling studies (Alcantara Llaguno et al, 2015) suggests that both multipotent neural stem cells (NSCs) and lineage-restricted oligodendrocyte precursor cells (OPCs) are capable of giving rise to anatomically and molecularly unique types of GBM when transformed with identical mutations (i.e., Tp53 , Pten , Nf1 deletion) using cell specific Cre-drivers ( Nestin creER for NSCs, Ascl1 creER for NSC/OPCs, Cspg4 creER for OPCs). These authors observed expression of Olig2 in both Type I (‘NSC’-like) and Type II (‘OPC-like’) tumors in their genetically engineered mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Intratumoral heterogeneity, diffuse infiltration throughout the brain parenchyma, and resistance to traditional therapies pose a major clinical challenge, which inevitably leads to tumor recurrence and the demise of the patient (Cloughesy et al, 2014). Recent work has highlighted the epigenetic and transcriptional networks of GSCs in human GBM (Suva et al, 2014), and their resemblance to niche-restricted progenitors of the adult mammalian brain (Alcantara Llaguno et al, 2015). Due to their unique ability to self-renew and differentiate into the neuro-glial lineages of the central nervous system (CNS), GSCs present a therapeutic burden by sustaining intratumoral heterogeneity and resistance to traditional therapies (Lathia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To amplify the output of each division, stem cells generate intermediate progenitors that possess restricted developmental potential, and produce exclusively differentiated cell types (Paridaen and Huttner, 2014). If their developmental potential is not stably restrained, intermediate progenitors may become susceptible to oncogenic transformation (Alcantara Llaguno et al, 2015; Chen et al, 2010). Thus, the mechanisms that restrict the developmental potential of intermediate progenitors must be executed in an extremely efficient and robust manner to ensure normal development and tissue homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…His work explored the stem cell origin of CSCs in malignant glioma and utilized the CDG transgene in specific promoter elements to target both CSCs and transit-amplifying cells. This discovery implicates that same genetic drivers in different cells of origin develop distinct glioblastoma multiforme (GBM) tumor types (6). …”
Section: Cancer Stem Cell Overviewmentioning
confidence: 99%
“…Furthermore, high-throughput screenings may help better determine the best personalized approach to treat patients. In addition, examining genomic alterations at premalignant stages (6, 7) could identity malignancy-specific targets.…”
Section: Clinical Trials Of Csc Targeting Therapeuticsmentioning
confidence: 99%